Correlation of Self Concept and Students’ Motivation at University of Cokroaminoto Palopo - Ahmad Adiwijaya (Universitas Cokroaminoto Palopo, 2015)
Self – concept and motivation are two important terms in educational world. Self concept is a one of dominant factor influences the students motivation in learning Englsih as foreign or second language. Therefore, the purpose of this study is to describe: the correlation between self concept and students’ motivation at English students of Cokroaminoto Palopo University. The research used correlational design. The population was the sixth semester of English Departement of Cokroaminoto Palopo University. The sample of this research was selected by using random sampling. The collection of the data was done by using questionnaire. The result of the research shows that there is a significant correlation between self concept and students motivation in learning English at English Departement of Cokroaminoto Palopo University. It can be concluded that the correlation between self concept and students’ motivation is significant. The significant was smaller than 0.05 . it indicates that if self concept of students increases, therefore students motivation also increases.